Influence of laser peening without coating on microstructure and fatigue limit of Ti-15V-3Al-3Cr-3Sn. (April 2019) - Rajan, S. Sudhagara; Manivasagam, Geetha; Ranganathan, Mohan; Swaroop, S.
Highlights: LPwC induced α precipitation is observed through EBSD studies. LPwC induced CRS is found till the maximum depth of 150 µm. Observed increased fraction of low angle grain boundaries in the peened sample. LPwC yielded a higher number of runout samples in the fatigue studies. Fractography revealed the least influence of laser peening induced surface features. Abstract: In the present study, Ti-15V-3Al-3Cr-3Sn (Ti-15-3), a beta titanium aerospace alloy in solution treated condition (850 °C/1 h) was subjected to Laser Peening without Coating (LPwC) with a wavelength of 532 nm and power density of 8.96 GW cm −2 . Surface roughness was analysed using 3D optical topography. Curiously, in the near peened surface, peening induced precipitation (i.e. 19% of α precipitation) and increased fraction of low angle boundaries (∼123%) was revealed through the Electron Back Scattered Diffraction (EBSD) analysis. Through depth nanohardness measurement was carried out along the cross-section of the peened sample right from the near peened surface. Peak hardness of 4.6 GPa is observed at a depth of 100 µm from the peened surface while the base/bulk hardness of the material is 4 GPa. In addition, X-Ray Diffraction (XRD) based analysis confirmed the presence of compressive residual stress in the near surface region of the peened sample. To understand the effect of the peening induced microstructural changes and residual stresses in fatigue behaviour, staircase method of fatigue analysis was adopted and observed that the more number of run out samples belonged to laser peened condition when compared to the unpeened condition. Despite this favourable indication, fatigue limit remains more or less unaltered even after peening. Fractography studies revealed the least influence of the surface roughness induced by laser peening over the crack initiation. Irrespective of the condition (i.e. unpeened and laser peened), crack initiation was predominantly influenced by the stress concentration co-existing at the sharp corners.